Current Advances in Meat Nutritional, Sensory and Physical Quality Improvement - Picard, Brigitte (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Within the idea and objective of bringing together original studies dealing with the continuum aspects of meat, i.e., from farm to fork, this book grouped papers on the study of the nutritional, sensory, and technological aspects of carcass, muscle, meat, and meat-product qualities. This nook highlights a great part of the research activities in the field of meat science. A total of 14 original studies and one comprehensive review were edited within five main topics: (i) production systems and rearing practices, (ii) prediction of meat quality, (iii) statistical approaches for meat quality prediction/management, (iv) muscle biochemistry and proteomics techniques, and (v) consumer acceptability, development, and characterization of meat products.